Implementation of Blue Economy in Improving Community Welfare in the Coastal Area of Berau Regency - Susanti, Endah; Puspitasari, Lisa (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Berau Regency is one of the areas that has good marine economic potential and natural wealth. To sustain its resilience and carrying capacity, marine natural resources must be explored based on the principles of sustainable development. The concept of the blue economy is considered as one of the solutions to bridge economic interests and the preservation of the marine environment. This article seeks to review the implementation of the blue economy concept in the development of coastal communities in Berau Regency, in particular improving the welfare of community through the implementation of the blue economy. The results of observations show that if the marine potential in Berau Regency has begun to be developed based on the blue economy principle, the conservation area established by the Berau Regency government plays an important role in the process of nature conservation,